Infant cultures of Pantanal children in a school context: protagonism as an development of local culture element - Brostolin, Marta Regina (2023)
The Pantanal region of Mato Grosso do Sul, through the implementation of its farm schools, opens up possibilities for investigation and, in this context, this text emerges, presenting an excerpt of doctoral research. The investigation, with a qualitative approach and ethnographic nature, had as subjects children from a farm located in the municipality of Aquidauana, state of Mato Grosso do Sul. The text in question aims to identify the re(creations) and appropriations of Pantanal children in infant games, in a school context, illustrative of their protagonism and landmark of the local culture. It is anchored in the assumptions of the Sociology of Childhood, which recognizes children as social actors, protagonists of their life stories. It uses participant observation, field notebook, photographs, and conversation circles for data collection, as a way of getting to know the group and interacting during their games, which manifest children's protagonism. The results show that Pantanal children, through interactive actions in their games, carry individual knowledge built in the daily experiences of their broader social and cultural worlds and, in some way, assume shared elements of interaction with other children and adults, thus generating the re(creations) and appropriations of their Pantanal lives.